Concrete foundations for turbine generators : analysis, design, and construction - Liu, Hongchun (American Society of Civil Engineers, 2018)
Sponsored by the Energy Division of ASCE. The design of turbine-generator foundations requires advanced technical expertise in structural engineering and soil dynamics, as well as close collaboration with manufacturers, mechanical and electrical engineers, and plant designers. Various manufacturers have different requirements for such foundations, and application of code provisions can demand a significant degree of interpretation. Concrete Foundations for Turbine Generators: Analysis, Design, and Construction provides the practical assistance needed by structural engineers and facility owners to meet these challenges with the most up-to-date and reliable information available. This Manual of Practice addresses the design of three types of concrete foundations for turbine generators: block foundations, with pedestals, piers, and blocks supported on a common mat foundation (basemat); elevated space-frame pedestal foundations, with columns, walls, and a tabletop supported on the basemat; and foundations where equipment or structural elements are supported on a vibration-isolation system. Topics include turbine generator equipment, foundation layout and sizing, foundation loads and load combinations, modeling of soil and pile response to dynamic loads, finite element modeling, serviceability analysis and acceptance criteria, strength and stability design, embedded items, vibration-isolated foundations, and construction considerations. Three appendixes on dynamic impedance discuss soil-supported rigid foundations, pile-supported foundations, and calculation examples. MOP 136 delivers state-of-the-practice guidance on turbine-generator foundations for structural design engineers, operating company personnel responsible for establishing structural design criteria and construction standards, and local building officials.
"Sponsored by the Energy Division of the American Society of Civil Engineers."
Keywords: Turbogenerators -- Foundations -- Design and construction.; Steam-turbines -- Foundations -- Design and construction.; Concrete footings -- Design and construction.; elektronické knihy; electronic books